12c+11c+-3(10c+12)=

Simple and best practice solution for 12c+11c+-3(10c+12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12c+11c+-3(10c+12)= equation:


Simplifying
12c + 11c + -3(10c + 12) = 0

Reorder the terms:
12c + 11c + -3(12 + 10c) = 0
12c + 11c + (12 * -3 + 10c * -3) = 0
12c + 11c + (-36 + -30c) = 0

Reorder the terms:
-36 + 12c + 11c + -30c = 0

Combine like terms: 12c + 11c = 23c
-36 + 23c + -30c = 0

Combine like terms: 23c + -30c = -7c
-36 + -7c = 0

Solving
-36 + -7c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + -7c = 0 + 36

Combine like terms: -36 + 36 = 0
0 + -7c = 0 + 36
-7c = 0 + 36

Combine like terms: 0 + 36 = 36
-7c = 36

Divide each side by '-7'.
c = -5.142857143

Simplifying
c = -5.142857143

See similar equations:

| 8x-8y=-1 | | -1.7=1.2-x | | S=19.26+22.43 | | 3(2x+5)=3 | | 5(x+8)=x | | 14.95V+16.88C=112.37 | | 3x=5(x+2) | | b(b+17)=0 | | -1=-2r+8 | | 2+6+5n+7n+3+7n= | | 0=4r^2-28+49 | | 36a^2-84at+49t^2=0 | | 5x^3y^2-2x^3y^5+3x^2y-7xy-1=0 | | 500+370= | | n+3N=164 | | (x-.20)=80.80 | | Y=.75x+75 | | 10a^3+4a^2+5a+2= | | 3t^2-16=22t | | -7n-9+3n= | | r^2+4r=0 | | 8-2x=2+x | | 2x-5(x-13)=35 | | 2(2x-4)=392x-4 | | 12X+54000=15X | | 13X+48000=16X | | 2q=-10 | | -3-2+(-8)-5= | | 16x+20y=24 | | 5n-3=6n+8 | | 2x^2+36x+100=0 | | (2w-4)w=160 |

Equations solver categories